Caregiving Burden in Family Caregivers Of Patients With Schizophrenia Post-Pasung in Jember - Lusi Padma Sulistianingsih Mata; Inke Kusumastuti; Ida Sri Surani Wiji Astuti; Sheilla Rachmania (Journal of Agromedicine and Medical Sciences, 2023)
Pasung (restrain) towards people with schizophrenia has yet to recede from being a complex problem in Jember, East Java. One of many aspects of pasung that has not been widely studied is the caregiving burden in the post-pasung period. This research aimed to comprehend the meaning-making of the caregiving phenomenon as experienced by the families of people with schizophrenia during the patients’ post-pasung period in Jember. This research utilizing the interpretive phenomenological analysis (IPA) recruited 11 participants (7 caregivers of people with schizophrenia and 4 community mental health nurses) who were purposively sampled and underwent semistructured interviews from November to December 2019. Two themes emerged in this study namely the experience of the post-pasung caregivers and triangulation with the community mental health nurses which consisted of 8 and 3 subthemes, respectively. Post-pasung caregiving burden experienced by families in this study consisted of subjective, objective, and iatrogenic burdens. Compared with the pasung period, the burden was lighter both for objective and subjective caregiving burden. The most dominating burden is the subjective burdens including apprehensiveness, stigma from the family and the society, and advice from external parties that were against the process of recovery and the objective burden came in the form of the caregiver’s significant health problems. Caregivers made various efforts supported by the provision of accessible and holistic health services as well as interdisciplinary coordination to ease the burden. This study indicates the diversity of the caregiving burden of post-pasung people with schizophrenia. This diversity suggests that interventions aimed at lightening the burden should be carefully selected based on the actual needs of the caregivers. Keywords : caregiving burden, caregivers, pasung, schizophrenia